2021
DOI: 10.1200/op.20.00619
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic Surge on Radiation Treatment: Report From a Multicenter New York Area Institution

Abstract: PURPOSE: During the COVID-19 surge months of March and April 2020, our New York multicenter health system experienced an influx of cases with COVID-19. We sought to study the impact of the surge period on patients with cancer prescribed radiation treatment (RT). METHODS: We reviewed our secure departmental quality assurance database for all patients who underwent RT planning simulations from March 6, 2020, through April 30, 2020. A priority level between 1 and 3 was prospectively assigned to each case based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Regarding radiotherapy treatments, 57 indicators from 8 articles [55,90,92,121,135–138] were identified. Most of these indicators signalled a reduction of the number of treatments (n=41, 72%), namely in UK, US, and Canada.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding radiotherapy treatments, 57 indicators from 8 articles [55,90,92,121,135–138] were identified. Most of these indicators signalled a reduction of the number of treatments (n=41, 72%), namely in UK, US, and Canada.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen indicators (38%) signalled stable waiting times and 8 (19%) a reduction in time to treatment. Twenty-one surveys [58,70,84–86,88,108,109,114,117,132–134,141,147–153], 2 studies using administrative data and surveys [121, 138] and 1 prospective study [117] reported on delays in cancer treatment. From those, eleven articles were international studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the patients are at a greater risk of serious complications from a COVID-19 infection, largely due to comorbidities ( 1 ), and recent treatment may be a risk factor for a severe course of COVID-19 ( 2 , 3 ). Due to staffing challenges and risk of disease transmissions, radiotherapy treatments have been postponed, interrupted, shortened using hypo-fractionation or even cancelled ( [4] , [5] , [6] , [7] , [8] , [9] ). The impact of the pandemic, of course, depending on the regional effect of the pandemic.…”
Section: Introductionmentioning
confidence: 99%